Longitudinal analysis of immunocyte responses and inflammatory cytokine profiles in SFTSV-infected rhesus macaques - Li, Yi-Hui; Huang, Wen-Wu; He, Wen-Qiang; He, Xiao-Yan; Wang, Xue-Hui; Lin, Ya-Long; Zhao, Zu-Jiang; Zheng, Yong-Tang; Pang, Wei (Frontiers in Immunology, 2023)
Severe fever with thrombocytopenia syndrome virus (SFTSV), an emerging bunyavirus, causes severe fever with thrombocytopenia syndrome (SFTS), with a high fatality rate of 20%–30%. At present, however, the pathogenesis of SFTSV remains largely unclear and no specific therapeutics or vaccines against its infection are currently available. Therefore, animal models that can faithfully recapitulate human disease are important to help understand and treat SFTSV infection. Here, we infected seven Chinese rhesus macaques (Macaca mulatta) with SFTSV. Virological and immunological changes were monitored over 28 days post-infection. Results showed that mild symptoms appeared in the macaques, including slight fever, thrombocytopenia, leukocytopenia, increased aspartate aminotransferase (AST) and creatine kinase (CK) in the blood. Viral replication was persistently detectable in lymphoid tissues and bone marrow even after viremia disappeared. Immunocyte detection showed that the number of T cells (mainly CD8+ T cells), B cells, natural killer (NK) cells, and monocytes decreased during infection. In detail, effector memory CD8+ T cells declined but showed increased activation, while both the number and activation of effector memory CD4+ T cells increased significantly. Furthermore, activated memory B cells decreased, while CD80+/CD86+ B cells and resting memory B cells (CD27+CD21+) increased significantly. Intermediate monocytes (CD14+CD16+) increased, while myeloid dendritic cells (mDCs) rather than plasmacytoid dendritic cells (pDCs) markedly declined during early infection. Cytokines, including interleukin-6 (IL-6), interferon-inducible protein-10 (IP-10), and macrophage inflammatory protein 1 (MCP-1), were substantially elevated in blood and were correlated with activated CD4+ T cells, B cells, CD16+CD56+ NK cells, CD14+CD16+ monocytes during infection. Thus, this study demonstrates that Chinese rhesus macaques infected with SFTSV resemble mild clinical symptoms of human SFTS and provides detailed virological and immunological parameters in macaques for understanding the pathogenesis of SFTSV infection.